Central pontine myelinolysis: correlation between CT and electrophysiologic data. - Sztencel, J; Baleriaux, D; Borenstein, S; Brunko, E; Zegers de Beyl, D (American Journal of Neuroradiology, 1983)
Because of the nature and location of the lesion in central pontine myelinolysis, considerable difficulties in diagnosis may arise. Computed tomography (CT) and brainstem auditory-evoked potentials are useful in following the spread and regression of the pontine lesion. The correlation between clinical evolution, serial CT scans, and brainstem auditory-evoked potentials is considered in a patient with central pontine myelinolysis and subsequent complete recovery with special emphasis on the evolution of the CT scan after recovery.